It's no party with these - Abd Razak, Dzulkifli (2005)
IT is indeed tragic to read about the death of our youths following the (mis)use of a cocktail of designer drugs, including Ecstasy, which are wrongly dubbed as "party drugs" (NST, June 12). The recent report linking seemingly innocuous "painkillers" to heart attacks because of prolonged use is a case in point (NST, June 11). A recent study in Britain showed that a number of common painkillers, taken daily by hundreds of thousands of arthritis patients, raises significantly the risk of a heart attack. The class of drugs involved in clude ibuprofen, diclofenac and naproxen. The newer ones are celecoxib and rofecoxib.